Hyperkalemia in a Hemolyzed Sample in Pediatric Patients: Repeat or Do Not Repeat?. Issue 1 (29th January 2023) - Kaila, Rahul; Hendrickson, Marissa; Avendano, Pablo; Davey, Cynthia; Cullen, Ryan; Colbenson, Gretchen; Louie, Jeffery
Abstract : Objective: The aim of the study is to analyze whether repeat testing is necessary in healthy children presenting to a pediatric emergency department (ED) who are found to have hyperkalemia on a hemolyzed specimen. Methods: A 5-year retrospective analysis of pediatric ED patients found to have elevated potassium values on laboratory testing of a sample reported to be hemolyzed. All patients aged 0 to 17 years who had an elevated potassium level after an intravenous draw resulted from a serum sample that was reported as hemolyzed during an ED visit were included in the study. Results: One hundred eighty-seven patients with some degree of both hemolysis and hyperkalemia were included in the final analysis. The median age was 1.9 years of age. The most common race among all patients was White, followed by African American, and Asian. One hundred forty-five children had repeat sampling for hemolyzed hyperkalemia, 142 children, 97.9% (95% confidence interval, 95.6%–100%) had a normal potassium on repeat and 3 children, 2.1% (95% confidence interval, 0.0%–4.4%) had true hyperkalemia. The frequency of true hyperkalemia in our study population was 2% (3/145). All 3 of these patients had underlying conditions that would appropriately have raised clinician suspicion for hyperkalemia. Conclusions: It may be unnecessary to obtain repeat samples to confirm normal potassium in a hemolyzed sample with normal blood urea nitrogen and creatinine.